Physical and mechanical properties of rubber wood from Karnataka - Kamala B S; Rao P V K (Indian Journal of Natural Rubber Research, 1993)
Strength properties in green and air dry conditions based on tests conducted on small clear speciments obtained from eight logs of Hevea brasiliensis (rubber) wood from Sullia region of Karnataka have been reported. The comparative suitability indices and safe working stresses have also been evaluated and reported. The results obtained have been compared with rubber wood from Kerala and Malaysia. The strength properties of rubber wood from Karnataka were slightly higher than those of Kerala rubber wood and less than those of Malaysian rubber wood. Rubber wood from spent Hevea brasiliensis trees could be efficiently used for a variety of uses such as furniture, door and window shutters, manufacture of packing cases, tool handles, etc.
Keywords: Hevea brasiliensis; Karnataka; Mechanical properties; Rubberwood